Statistical thinking : improving business performance - Hoerl, Roger Wesley; Snee, Ronald D. (Hoboken, N.J. : John Wiley & Sons, 2012)
"How statistical thinking and methodology can help you make crucial business decisions. Straightforward and insightful, Statistical Thinking: Improving Business Performance, Second Edition, prepares you for business leadership by developing your capacity to apply statistical thinking to improve business processes. Unique and compelling, this book shows you how to derive actionable conclusions from data analysis, solve real problems, and improve real processes. Here, you'll discover how to implement statistical thinking and methodology in your work to improve business performance. Explores why statistical thinking is necessary and helpful. Provides case studies that illustrate how to integrate several statistical tools into the decision-making process. Facilitates and encourages an experiential learning environment to enable you to apply material to actual problems. With an in-depth discussion of JMP software, the new edition of this important book focuses on skills to improve business processes, including collecting data appropriate for a specified purpose, recognizing limitations in existing data, and understanding the limitations of statistical analyses"--
pt. 1. Statistical thinking concepts -- pt. 2. Statistical engineering : frameworks and basic tools -- pt. 3. Formal statistical methods.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Commercial statistics; BUSINESS & ECONOMICS -- Statistics; Commercial statistics; x